Modeling Werner Syndrome in Drosophila melanogaster: hyper-recombination in flies lacking WRN-like exonuclease. - Cox, L; Clancy, D; Boubriak, I; Saunders, R (2007)
Human progeroid Werner syndrome provides the current best model for analysis of human aging, recapitulating many aspects of normal aging as a result of mutation of the WRN gene. This gene encodes a RecQ-type helicase with additional exonuclease activity. While biochemical studies in vitro have proven invaluable in determining substrate specificities of the WRN exonuclease and helicase, it has been difficult to dissociate the two key enzyme activities in vivo. We are developing Drosophila as a model system for analysis of WRN function; the suitability of Drosophila for extensive and sophisticated genetic manipulation permits us to investigate regulatory pathways and the impact of WRN loss at organismal, cellular, and molecular levels. BLASTP screening of the Drosophila genome with human WRN sequence allowed us to identify three RecQ helicases with strong homology to human WRN, a presumed helicase component of the spliceosome, and two DEAH-box putative RNA helicases with weaker WRN homology. None of these helicases contain a WRN-like exonuclease domain, but two potential WRN-like exonucleases in flies encoded by the loci CG7670 and CG6744 were also identified in the BLAST search. CG6744 and CG7670 are more closely related to human WRN than to each other. We have obtained a fly strain with a piggyBac insertional mutation within the CG6744 locus, which decreases expression of the encoded mRNA. Such flies show elevated levels of somatic recombination. We suggest that WRN-like exonuclease activity is critical in maintaining genomic integrity in flies.